Carbon budget at the individual-tree scale: dominant Eucalyptus trees partition less carbon belowground - Fernandez Tschieder, Ezequiel; Marshall, John D.; Binkley, Dan (Wiley, 2024)
Large trees in plantations generally produce more wood per unit of resource use than small trees. Two processes may account for this pattern: greater photosynthetic resource use efficiency or greater partitioning of carbon to wood production. We estimated gross primary production (GPP) at the individual scale by combining transpiration with photosynthetic water-use efficiency of Eucalyptus trees. Aboveground production fluxes were estimated using allometric equations and modeled respiration; total belowground carbon fluxes (TBCF) were estimated by subtracting aboveground fluxes from GPP. Partitioning was estimated by dividing component fluxes by GPP. Dominant trees produced almost three times as much wood as suppressed trees. They used 25 ± 10% (mean ± SD) of their photosynthates for wood production, whereas suppressed trees only used 12 ± 2%. By contrast, dominant trees used 27 ± 19% of their photosynthate belowground, whereas suppressed trees used 58 ± 5%. Intermediate trees lay between these extremes. Photosynthetic water-use efficiency of dominant trees was c. 13% greater than the efficiency of suppressed trees. Suppressed trees used more than twice as much of their photosynthate belowground and less than half as much aboveground compared with dominant trees. Differences in carbon partitioning were much greater than differences in GPP or photosynthetic water-use efficiency.